Factors affecting the uptake of prenatal diagnosis for sickle cell disease. Issue 11 (November 1992) - Petrou, M; Brugiatelli, M; Ward, R H; Modell, B
Abstract : Between 1979 and 1990, 170 couples at risk of having children with sickle cell disease, resident in the UK and with a continuing pregnancy, were referred for counselling at the University College Hospital Perinatal Centre. Approximately 50% of the couples, including those where one partner actually had sickle cell disease, requested prenatal diagnosis. This was requested in 82% of pregnancies when the mother was seen in the first trimester of pregnancy and in 49% when she was seen in the second trimester. More than 90% of referred couples who already had an affected child requested prenatal diagnosis. The type of sickle cell disease involved and ethnic group also influenced choice. These results show the importance of detecting and counselling couples at risk before pregnancy whenever possible.